2020
DOI: 10.4158/accr-2019-0487
|View full text |Cite
|
Sign up to set email alerts
|

Unique Presentation of Duplication of the Pituitary Gland-Plus Syndrome

Abstract: Objective: To shed light on a unique presentation of duplication of the pituitary gland (DPG)-plus syndrome. Methods: We present the case report gathered from the patient. Results: This patient uniquely had DPG-plus syndrome with a concurrent dermoid cyst. Conclusion: DPG is a very rare developmental anomaly and there are not many case reports published in the literature. The presence of DPG with dermoid cyst in our patient has not been reported previously. This case report discusses the various presentations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Therefore, the characteristic thickening of the floor of the third ventricle extending from the median eminence to the mammillary bodies, which is easily visible on midline sagittal MR image of our patient, might be related to duplication of that hypothalamic nuclei. This occurrence could explain the appearance of the endocrine alterations later in life ( 2 ).…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Therefore, the characteristic thickening of the floor of the third ventricle extending from the median eminence to the mammillary bodies, which is easily visible on midline sagittal MR image of our patient, might be related to duplication of that hypothalamic nuclei. This occurrence could explain the appearance of the endocrine alterations later in life ( 2 ).…”
Section: Discussionmentioning
confidence: 95%
“…DPG-plus syndrome is a rare condition with only 52 cases described worldwide and few MRI studies reported ( 1 , 2 ). The rarity of this entity may hence be partially attributable to incidental detection on imaging and early mortality in some patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations